Antisystemic Movement Analysis: Tracing the World-Scale Determinants of Syndicalism. (28th February 2017) - MacPherson, Robert
Abstract: World-systems scholars have recently advanced a framework for the analysis of "antisystemic" movements, with one important component of this approach being the integration of global forces into causal accounts of social movement mobilizations. This perspective, both an extension and a critique of existing movement theories such as political opportunity structure and political mediation approaches, is an outgrowth of the long-running trend of constructing larger and more elaborate models of the economic and political structures that bear upon movement outcomes. I elaborate three strategies of antisystemic movement analysis, and go on to combine these strategies with Event Structure Analysis (ESA) in order to investigate episodes of syndicalist mobilization in Argentina in 1917 and Chile in 1923. These cases reveal a set of crucial world-scale determinants at work in each mobilization: the relations between local and foreign capitalists, fluctuations in the world market transmitted through foreign-dominated enclaves, and direct and indirect influence by powerful core states such as Britain and the US. In contrast to the sorts of nationally-bound causality assumed in many social movement theories, I demonstrate that these world-scale forces cannot be included merely as external context; instead, they actively condition ostensibly "local" actors and are crucial determinants of each mobilization's shape.